Research and Design of Standard System for Electric Drying - LU Hao-peng; CHENG Ling; BU Fan-peng (Liang you shipin ke-ji)
Facing the new goals of “carbon peaking” and “carbon neutrality”, increasing the electrification level of energy consumption is of great significance for ensuring food security, promoting green transformation in agriculture, and achieving energy conservation and emission reduction. Drying is a crucial link in safeguarding food security, and electric drying can better improve industrial energy efficiency and safeguard food security. Therefore, to standardize the work of electric drying technology, it is necessary to conduct research on its standard system. Based on extensive collection and in-depth analysis of relevant domestic and international standards, a comprehensive and in-depth induction and research on the standard system of electric drying technology has been carried out from the two sub-domains of basic standards and specialized standards. Combining the principles of standard construction for power substitution technologies, the standard requirements of electric drying technology in different application scenarios have been deeply analyzed, and a conceptual model of the electric drying standard system with clear logic and rigorous structure has been constructed. Based on the conceptual model, the overall framework of the electric drying standard system has been extracted, laying a solid foundation for the standardized development of electric drying technology. Moreover, from a forward-looking perspective, planning suggestions for the future development of the electric drying standard system have been put forward.